Praktyki pedagogiczne i ich rola w rozwijaniu umiejętności interpersonalnych u kandydatów do zawodu nauczycielskiego = Teaching practices and their role in developing interpersonal skills of candidates for the teaching profession - Żuchelkowska, Krystyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Teaching practices are an important part of teacher education. They create an opportunity to apply theoretical knowledge in practice, allow candidates to become familiar with the specificity of the teacher`s profession, help develop professional competences, and provide a broader outlook on education. It is possible to say thus that good teaching practices are the best teacher.
Keywords: praktyki pedagogiczne; umiejętności interpersonalne; teaching practices; interpersonal skills